Análise da matriz energética brasileira sob a visão sistêmica: programas energéticos governamentais e a redução de gases de efeito estufa - Lückemeyer, Alfonso Celso Arruda Bianchini (2010)
This thesis proposed as subject of study an overview of renewable and less pollutant energy in Brazil, focusing on global climate change, specifically the emission of greenhouse gases. The objective of the research is to analyze the Brazilian energy matrix with respect to the relation between the supply of renewable energy, regulated by governmental policies and programs, and the issue of greenhouse gases. This analysis is made through a contextualization of the Brazilian energy matrix in the world scene, of the relation between the uses of energy and global climate change, and of the analysis of energy programs in Brazil and their contribution to minimize the emission of air pollutants. For this study, a historical survey was conducted, by means of literature review, on the use of energy and governmental energy programs, energy supply, CO2 emissions and scenarios for the year 2030, international agreements and mechanisms for climate change mitigation, sectors of Brazilian society that consume more energy and what are the sources they use, renewable energy technologies available and the climate damage caused by them in energy processes. The systemic epistemological view has based this thesis, since this method was suitable for the managing of the energy issue for the game of harmonization among natural resources, consumption and climate damage, based on the view of an ecossocioeconomia. The main results showed that it is possible to increase the share of less pollutant and renewable energy such as wind, solar, small hydropower plants and biomass in the Brazilian energy matrix and promote energy efficiency in order to increase the supply of energy, reducing the need of using natural energy resources and the consequent environmental impact. It was noted that governmental energy policies and programs contribute to encourage the use of renewable energy and to improve levels of air pollutants. It was concluded that, in order to reduce the emission of greenhouse gases from energy processes while guaranteeing the continuity of economic development, a set of measures is necessary, including: gradual replacement of fossil fuels in energy matrix by renewable sources, in association with energy efficiency, and integrated and viable governmental programs in political, economic, technological and socio-environmental terms. It was observed that there is an interplay of forces involving energy between socio-environmental and economic development and, therefore, at present and near future there is no way to rule out the use of totally non-renewable energy (thermoelectric power plants run by fossil fuels and nuclear energy, and fossil fuels for the transportation sector), considering the need to address the issue of energy safety.